3D printing and bioprinting in the battle against diabetes and its chronic complications - Sathisaran, Indumathi (Frontiers in Bioengineering and Biotechnology, 2024)
Diabetes is a metabolic disorder characterized by high blood sugar. Uncontrolled blood glucose affects the circulatory system in an organism by intervening blood circulation. The high blood glucose can lead to macrovascular (large blood vessels) and microvascular (small blood vessels) complications. Due to this, the vital organs (notably brain, eyes, feet, heart, kidneys, lungs and nerves) get worsen in diabetic patients if not treated at the earliest. Therefore, acquiring treatment at an appropriate time is very important for managing diabetes and other complications that are caused due to diabetes. The root cause for the occurrence of various health complications in diabetic patients is the uncontrolled blood glucose levels. This review presents a consolidated account of various types of three-dimensional 3D (Bio)printing technologies and its applications in treating diabetes as well as the complications caused due to impaired blood glucose levels. Herein, the development of biosensors (for the diagnosis), oral drug formulations, transdermal drug carriers, orthotic insoles and scaffolds (for the treatment) are discussed. Next to this, the fabrication of 3D bioprinted organs and cell-seeded hydrogels (pancreas engineering for producing insulin and bone engineering for managing bone defects) are discussed. As the final application, 3D bioprinting of diabetic disease models for high-throughput screening of antdiabetic drugs are discussed.